Cyclic behaviour modelling of GFRP adhesive connections by an imperfect soft interface model with damage evolution. (1st January 2022) - Lamberti, M.; Maurel-Pantel, A.; Lebon, F.; Ascione, F.
Abstract: In this paper a methodology for studying the mechanical behaviour of complex structures made of GFRP structural members joined by means of adhesive connections and subject to variable intensity loads is presented. The fundamental equations are derived by an asymptotic approach applied on composite structures made of two elastic solids bonded together by a third thin one represented by a thin layer with a nonlinear behaviour. The adhesive layers are considered micro cracked according to the Kachanov's assumptions. Within this framework, to calibrate the parameters of the imperfect interface model, the mechanical properties and damage evolution of an epoxy adhesive have been experimentally evaluated under cyclic loadings. The experimental tests have been performed on aluminium cylinders considering different thicknesses of adhesive. The experimental results evidence how the adhesive thickness influences the strength, stiffness and consequently the initial damage parameter (initial cracks) of the bonded connections. Finally, the robustness and accuracy of the imperfect interface model is demonstrated by the excellent comparison with experimental results of a GFRP hollow column to built-up beam adhesive connection, under static, cyclic and fatigue loads using a description of damage evolution.